Verifying integrity of exception handling in service-oriented software. (2017) - Xue, Tong; Ying, Shi; Wu, Qing; Jia, Xiangyang; Hu, Xiaohui; Zhai, Xiaoying; Zhang, Tao
In service-oriented software environments, that exceptions may not be fully handled is one of the main causes for system breakdown. Therefore, we need to verify integrity of software exception handling. At present verifying integrity of software exception handling mainly depends upon experiences of developer. Most of automatic formal verification mechanisms can only support some general features, such as equivalence, boundedness, security, etc. and easily cause state space explosion. This paper proposes an integrity verification method of exception handling in service-oriented software. We construct state spaces associated with exception handling and convert the issue of integrity verification into a model of boundedness analysis based on CPN, and reduce the size of state spaces by extending Stubborn Set and Transition Dependency Graph. An example and experimental results based on extended CPN tools confirm that our method has good generalisation abilities.